(untitled) (KMC Journal, 2025)
This study investigates the relationships of financial literacy, attitude, behavior, and personal financial management among college students in Rupandehi District of Nepal. The increasing financial challenges faced by students and the specific socio-economic context of Rupandehi district, understanding these relationships is crucial for promoting financial well-being. Drawing on the Theory of Planned Behavior and Behavioral Finance, the research hypothesized direct and mediated effects among these constructs. A quantitative study was conducted using a survey questionnaire administered to 500 college students from various institutions in Rupandehi. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal significant positive relationships among all variables. Financial literacy strongly predicts both financial attitude and behavior. Importantly, the results confirm that financial attitude significantly mediates the relationship between financial literacy and financial behavior. Furthermore, financial behavior is a significant mediator in the relationship between both financial literacy and financial attitude, and personal financial management. Financial literacy also has a direct positive effect on financial management. These results underscore that while financial knowledge is foundational, positive attitudes and responsible behaviors are essential pathways translating knowledge into effective financial management. The study supports all proposed hypotheses, emphasizing the need for holistic financial education programs that cultivate not just knowledge but also positive attitudes and practical habits. The findings have implications for educational institutions and policymakers aiming to enhance students’ financial capability in the region.